Anti-inflammatory activity of intravenous immunoglobulin through scavenging of heme. (July 2019) - Wiatr, Marie; Merle, Nicolas S.; Boudhabhay, Idris; Poillerat, Victoria; Rossini, Sofia; Lecerf, Maxime; Kaveri, Srini V.; Lacroix-Desmazes, Sébastian; Roumenina, Lubka T.; Dimitrov, Jordan D.
Abstract: Therapeutic intravenous immunoglobulin preparations (IVIg) are used for treatment of wide range of autoimmune and inflammatory diseases. Versatile mechanisms have been reported to contribute to the immunomodulatory effects of IVIg. Here we demonstrate that IVIg has a strong potential to inhibit pro-inflammatory effect of extracellular heme. Indeed, the presence of immunoglobulins reduced the potential of heme to activate the complement system on the surface of human endothelial cells. Since extracellular heme is considered as one of the principal pathogenic factors in hemolytic disorders, its therapeutic scavenging by IVIg may have significant clinical repercussions.